Comorbidity and polypharmacy impact neurobehavioral symptoms and symptom validity failure among post-9/11 veterans with mild traumatic brain injury - Swan, Alicia A.; Kennedy, Eamonn; Cooper, Douglas B.; Amuan, Megan E.; Mayo, Jamie; Tate, David F.; Song, Kangwon; Eapen, Blessen C.; Van Cott, Anne C.; Lopez, Maria R.; Pugh, Mary Jo (Frontiers in Neurology, 2023)
Objective: To examine the association of post-concussive comorbidity burdens [post-traumatic stress disorder (PTSD), depression, and/or headache] and central nervous system (CNS) polypharmacy (five or more concurrent medications) with reported neurobehavioral symptoms and symptom validity screening among Post-9/11 Veterans with a history of mild traumatic brain injury (mTBI). Setting: Administrative medical record data from the Department of Veterans Affairs (VA). Participants: Post-9/11 Veterans with mTBI and at least two years of VA care between 2001 and 2019 who had completed the comprehensive traumatic brain injury evaluation (CTBIE). Design: Retrospective cross-sectional study. Main Measures: Neurobehavioral Symptom Inventory (NSI), International Classification of Diseases, Ninth Revision, Clinical Modification diagnosis codes. Results: Of the 92,495 Veterans with a history of TBI, 90% had diagnoses of at least one identified comorbidity (PTSD depression, and/or headache) and 28% had evidence of CNS polypharmacy. Neurobehavioral symptom reporting and symptom validity failure was associated with comorbidity burden and polypharmacy after adjusting for socio-demographic characteristics. Veterans with concurrent diagnoses of PTSD, depression, and headache were more than 6 times more likely [Adjusted odds ratio = 6.55 (99% CI: 5.41, 7.92)] to fail the embedded symptom validity measure (Validity-10) in the NSI. Conclusions: TBI-related multimorbidity and CNS polypharmacy had the strongest association with neurobehavioral symptom distress, even after accounting for injury characteristics and socio-demographics. Given the regular use of the NSI in clinical and research settings, these findings emphasize the need for comprehensive neuropsychological evaluation for individuals who screen positively for potential symptom overreporting, the importance of multidisciplinary rehabilitation to restore functioning following mTBI, and the conscientious utilization of symptom validity measures in research efforts.